Arabia versus Persia: Is This What the Arab Spring Ended with? - Al Ganideh, Saeb; Yaseen, Saad (Journal of Comparative International Management, 2016)
The sectarian violence in the Middle East has changed the face of the Arab Uprisings and has extended violence between Sunni and Shiite Muslims to a wider scale. The current investigation explores economic and social implications of the Sunni-Shiite Muslim tension and competition to control the Middle East. The study aims to examine the influence of demographic and socio-physiological variables on feelings of animosity Arabs express towards Iran and purchasing Iranian products. The research design is quantitative. Data were collected from 108 Arab Sunni Muslim Jordanians who live in the capital of Jordan, Amman and the northern Irbid city over a period of 4 weeks, June, 2014. The results showed that younger Jordanians and Jordanians who express high level of internationalism hold less feelings of animosity against Iran than their other counterparts. Also, it was found that Jordanians’ feelings of animosity towards Iran have been translated into unwillingness to purchase Iranian products. Limitations of this research overall are related to employing a convenience sample and the relatively small sample size. Feelings of animosity Arab express toward Iran are not alarmingly high, nonetheless, such negative feelings should not be ignored by neither Iranian global marketers nor by Arab local marketers. To the best of the author’s knowledge, there is a death of studies that explored the social and business implications of the current Arab Spring events.